2022
DOI: 10.1101/2022.09.27.509719
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing the evolutionary drivers of nitrogen-fixing symbioses in challenging soil environments

Abstract: - While the importance of root nodular symbioses (RNS) in plants has long been recognized, the ecological and evolutionary factors maintaining RNS remain obscure. RNS is associated with environmental stressors such as aridity and nitrogen-poor soils; the ability to tolerate harsh environments may provide ecological opportunities for diversification, yet, nodulators are also diverse outside these environments. - We test several environmental determinants of increased survival and enhanced diversification of RNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 102 publications
1
21
1
Order By: Relevance
“…1C) was unexpected. Previous studies have supported aridity as favoring RNS (Pellegrini et al, 2016;Siniscalchi et al, 2022) and especially the phylogenetic diversity of RNS (Doby et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…1C) was unexpected. Previous studies have supported aridity as favoring RNS (Pellegrini et al, 2016;Siniscalchi et al, 2022) and especially the phylogenetic diversity of RNS (Doby et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
“…The copyright holder for this preprint (which this version posted April 18, 2023. ; https://doi.org/10.1101/2023.04.17.537249 doi: bioRxiv preprint 2019), so we elected to use a recent approach combining genomic data with all Fagales sequences available on GenBank (Siniscalchi et al, 2022). This tree, based on 20 regions from the nucleus, chloroplast, and mitochondrion, comprises 707 species of Fagales (60.2% of species-level diversity; Stevens, 2001 onwards) with complete genus-level representation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Root nodule symbiosis (RNS), a central adaptation in legumes, is intimately related to their predilection for arid open habitats (Sprent, 2007(Sprent, , 2009Sprent et al, 2017). A series of recent studies primarily focused on legumes (Adams et al, 2016;Doby et al, 2022;Pellegrini et al, 2016;Siniscalchi et al, 2022) has identified water stress as the preeminent driver of the geographic distribution of RNS, species richness, and phylogenetic diversity, reflecting the importance of nitrogen leaf economics for confronting drought challenge (Adams et al, 2016). This relationship suggests an important link between edaphic ecology and precipitation, with the former often seen as secondary in tropical forest ecology (Gentry, 1988).…”
Section: Introductionmentioning
confidence: 99%